2019
DOI: 10.1556/066.2019.48.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of overall and melamine migration from melamine bowls

Abstract: Overall and melamine migration have been determined for 60 samples of melamine resin bowls, which were purchased in various local markets in the area of Bursa, Turkey. The samples were exposed to food simulants 3% acetic acid, 10% ethanol aqueous solutions, and rectifi ed (refi ned) olive oil at 100 °C for 30 min, and 50% ethanol aqueous solutions at 60 °C for 30 min. The LOQ value was calculated as 3.3 mg dm -2 for overall migration and 0.126 mg kg -1 for melamine migration. Research fi ndings did not exceed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, these methods were never used to find a correlation between release of melamine or formaldehyde into food simulants or foodstuffs and the crosslinking of the resin. Nonetheless, an investigation [10] already stated a correlation between this release and price of the investigated samples; however, this was not confirmed by later studies [11].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, these methods were never used to find a correlation between release of melamine or formaldehyde into food simulants or foodstuffs and the crosslinking of the resin. Nonetheless, an investigation [10] already stated a correlation between this release and price of the investigated samples; however, this was not confirmed by later studies [11].…”
Section: Introductionmentioning
confidence: 79%
“…In the following years, melamine got more into the scientific focus [15,16] and Bradley et al confirmed that under acidic conditions at temperatures of 70 • C and higher, high amounts of melamine and formaldehyde might migrate or be released into food simulants [17,18]. In the following years, several studies more or less confirmed the earlier results [10,11,19,20].…”
Section: Introductionmentioning
confidence: 82%
“…Meanwhile, it is crucial to keep in mind that low emission-to-consumption ratios do not mean that molding compound products are harmless. This is because a significant amount of melamine may be released from the molding compound products or migrate into food at high temperatures and under high radiation conditions, given the popularity of automatic dishwashers and ultraviolet disinfection cabinets in Chinese families. , …”
Section: Resultsmentioning
confidence: 99%
“…This is because a significant amount of melamine may be released from the molding compound products or migrate into food at high temperatures and under high radiation conditions, given the popularity of automatic dishwashers and ultraviolet disinfection cabinets in Chinese families. 44,101 3.5. Scenario-Based Emission Estimation of Melamine in End-of-Life Products.…”
Section: Priority Analysis Of the Melamine Sourcesmentioning
confidence: 99%
“…Recent studies have reported detections of melamine in different matrices of water (river water (370 ng/L), lake water (347 ng/L), seawater (186 ng/L), tap water (512 ng/L), bottled water (98 ng/L)…) [ 8 ]. The migration of melamine into food occurs in measurable amounts, especially under acidic conditions and at high temperatures, and is also dependent on contact time [ 9 ]. On the other hand, melamine has sometimes been added as a non-protein nitrogenous additive to artificially increase the apparent “false” protein content in foodstuffs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%